1996
DOI: 10.1007/s004300050021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the human antibody response to outer surface protein C (OspC) of Borrelia burgdorferi sensu stricto, B. garinii, and B. afzelii

Abstract: The aim of this study was to determine by Western blotting (WB) the prevalence of anti-outer surface protein C (OspC) IgM and IgG antibodies in patients with Lyme borreliosis according to each of the three genospecies of Borrelia burgdorferi sensu lato. Strains of B. burgdorferi sensu stricto (MUL), B. garinii (DK 6), and B. afzelii (DK 26) served as antigen, all of which expressed abundant OspC. We examined sera from 117 patients with untreated early and late Lyme borreliosis, as well as from 100 blood donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
(34 reference statements)
3
18
0
1
Order By: Relevance
“…As a signi®cant heterogeneity has been described for OspC in European strains [35,38,39], one might reason that in this study an immune response to OspC and/or Osp17 was detected only in patients with B. afzelii infection. However, concerning OspC, we found that the IgM response is primarily directed against conserved epitopes [37], a ®nding con®rmed also by Mathiesen et al [23]. For Osp17, in can not be ruled out that heterogeneity may play a greater role compared to OspC.…”
Section: Lymphoproliferation To Lysate Antigenssupporting
confidence: 69%
“…As a signi®cant heterogeneity has been described for OspC in European strains [35,38,39], one might reason that in this study an immune response to OspC and/or Osp17 was detected only in patients with B. afzelii infection. However, concerning OspC, we found that the IgM response is primarily directed against conserved epitopes [37], a ®nding con®rmed also by Mathiesen et al [23]. For Osp17, in can not be ruled out that heterogeneity may play a greater role compared to OspC.…”
Section: Lymphoproliferation To Lysate Antigenssupporting
confidence: 69%
“…Mathiesen et al, who reported also that OspC of the B. garinii strain utilized by them was as sensitive alone as in combination with the OspCs of the representatives of the two other species (28). However, in an evaluation of IgG WBs with recombinant OspCs derived from the three species, OspC of PKo was the most sensitive and OspC of PBi was the least sensitive (42).…”
Section: Discussionmentioning
confidence: 99%
“…Highly passaged in vitro-cultured B. burgdorferi sensu lato does not express OspC, which explains why the importance of this antigen was unrecognized in early studies that used high-passage B. burgdorferi sensu lato as the source of antigen (63,70). OspC is heterogeneous, and amino acid differences exist among the sequences of OspC proteins from the different B. burgdorferi sensu lato species (135,197,336). Furthermore, intraspecies differences also exist; for example, at least 13 OspC serotypes have been identified in B. garinii by using a panel of monoclonal antibodies (361).…”
Section: Immunologic Diagnosis Of B Burgdorferi Sensu Lato Infectionmentioning
confidence: 99%
“…For example, OspC of B. garinii strains has better immunoreactivity than OspC of other B. burgdorferi sensu lato species in detecting IgM antibodies in patients with neuroborreliosis. This is most likely explained by the fact that B. garinii is the species that most frequently causes neuroborreliosis in Europe (197).…”
Section: Immunologic Diagnosis Of B Burgdorferi Sensu Lato Infectionmentioning
confidence: 99%